Meningkatkan Perkembangan Kognitif AUD Melalui Permainan Monoplay Box di TK Wisma Sari - Oktaviani, Ririn; Gede Anadhi, I Made; Komang Sindu Putra, Ida Bagus (UIR PRESS, 2024)
One of the important aspects of development in children is cognitive development which strengthens children's reasoning, how children manage information, how children overcome curiosity, children's self-management of difficulties encountered when they want to explore their high curiosity, apart from providing knowledge about things. -things around can also help children in terms of exporting their surroundings. The aim of this research is that children can sharpen their memory, intuition, focus and be able to solve problems independently using the monoplay box game media. The qualitative method is the method used to observe the subjects studied, namely 21 Kindergarten B1 children at Wisma Sari Kindergarten Denpasar. In accumulating the data used, namely observation, interviews and checklists. The gains obtained from this research can be seen from the Pre- Simulation period, 1st period, 2nd period and 3rd period after using the Monoplay Box game in the observations that have been made, it can increase the cognitive development of the aud through the Monoplay Box game with the results experiencing a significant increase.